Innovative Use of Tina Bed as a Cost-effective and Comfortable Dressing for Burn Wounds on the Torso: A Clinical Exploration - Vishal Kaundal; Ankur Dhirajlal Modi (Journal of Clinical and Diagnostic Research)
I would like to share an experience using Tina bed as an alternative dressing for burn wounds in a burn centre at a tertiary care facility. Typically used in hospitals to prevent bedsoiling from urine, Tina beds (under pads) have shown impressive fluid absorption and are often utilised in situations involving urinary incontinence, paediatric care and obstetric clinics [Table/Fig-1] [1]. Each Tina bed measures 60×90 cm and is cost-effective. The Tina bed comprises three distinct layers: the inner layer, a non woven cotton layer, promotes comfort; the intermediate layer, composed of an absorbent layer and gel, provides maximum absorbency while effectively managing moisture and odour; and the outermost layer, a polyethylene backing with sealed edges, ensures waterproof protection